Bacterial Degradation of Contaminated Soil using Organic Manure (2018)
Soil contamination is the presence in soil of unwanted impure materials from human activities. Many techniques of remediation of contaminated soils have been developed such as physical, chemical, photo degradation etc. Biological treatments offer the best environmental friendly method for remediating hydrocarbons and other contaminated soils because it utilized the capability of the indigenious micro-organisms in the environment to break down the hydrocarbons and heavy metals into innocuous substances. This study investigated the abilities of bacterial isolated, identified from organic manure and determine the total petroleum hydrocarbon degradative potentials. 2kg of soil was thoroughly mixed with 200ml and 400ml of spent oil to give 5% and 10% (w/w) each of organic manure ,poultry litter(PL),cow dung(CD) and mixed poultry litter and cow dung(MPLCD) was individually introduced into each spent oil contaminated soil and the rate of biodegradation was observed for a period of 12weeks.The percentage of total petroleum hydrocarbon (TPH) loss was significantly higher in the soil contaminated with 5% spent oil amended with MPLCD(40.46%) followed by PL (35.53%) and CD(27.70%) while 32.42% loss only was recorded in the soil contaminated with 10% spent oil and amended with MPLCD while PL was 30.04% and 25.60% for CD. The hydrocarbon-utilizing bacteria isolated band identified includes Bacillus, Pseudomonas, Microccus and Staphyloccus. The amendment spent oil contaminated soil with organic manure enhances the rate of degradation of petroleum hydrocarbon. These additives can best be suited to remove or neutralize the contaminants in the soil